Experimental Overview of Ethanol-Diesel Blends on Combustion of CI Engine - Ahmad Dimyani; Mulia Pratama; Arifin Nur; . Suherman; Achmad Praptijanto; Widodo Budi Santoso; Yanuandri Putrasari (New Approaches in Engineering Research Vol. 11, 2021)
This chapter explains in detail an experimental overview of the application of ethanol-diesel blends as fuel in a diesel engine. The experiment was carried out at various engine loads and ethanol percentages. The experiments were performed using neat diesel fuel, 2.5%, 5%, and 7.5% ethanol-diesel blends with 1,500 rpm of the engine working speed at three different loads namely 0, 10, and 40 Nm. Several engine parameters data such as torque, fuel consumption, cylinder pressure, air intake flow, engine coolant temperature, the exhaust gas temperature, lubricating oil temperature, and exhaust emission were collected. The combustion or heat release of the engine then was calculated and analyzed. The results show several interesting features from heat release phenomena in every combustion process from the different fuel blends. The results indicate that the increasing of ethanol fraction in the ethanol-diesel blends causes the maximum of cylinder pressure and the heat release value is also increased.